Assessment of the Safety Maturity Level if Construction Companies in Nigeria – EFQM Approach - Oladinrin, Olugbenga Timo; Chukwurah, Patrick Olisa; Makanjuola, Abayomi Sina (International Journal of Sustainable Construction Engineering and Technology, 2019)
Safety management culture/practices varies from country to country as well as company to company. Despite several efforts towards effective health and safety system in the construction industry in Nigeria, accident occurrences are still on the increase on construction sites. This study assesses the current maturity level of construction companies in Lagos State, Nigeria by introducing a form of self-assessment model to enable companies assess their performance with a view to offering suggestions on areas needing improvement. With the aid of structured questionnaire, the views of industry players were sought and analysed, chiefly with the use of factor analysis to group the attributes under the five factors of EFQM model. The results revealed that the construction companies in Lagos are currently at improver level according to the EFQM maturity scale. The study also revealed that people enabler factor contributes most to safety while leadership enabler is the least contributor. It was recommended that construction companies in Lagos should generally invest more on leadership and processes and resources enablers. Construction companies should evaluate their growth using self-assessment models and take stock of happenings and current level of activities and achievement for performance review and improvement.